PENERAPAN METODE DISCOVERY UNTUK MENINGKATKAN PRESTASI BELAJAR TENTANG LARI JARAK PENDEK - Winarto Winarto (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2015)
In the process of learning of Physical Education teachers are expected to teach a wide range of basic movement skills, techniques and strategy games and sports, internalization of values ​​(sportsmanship, honesty, cooperation, etc.) as well as the conditioning of healthy lifestyles. Activities are given in teaching should be to get a touch didactic-methodical, so that the activities are carried out can achieve the goal of teaching with the application discovery methods to improve learning achievement of the sprint. From the results of learning activities that had been performed for two cycles and based the entire discussion and analysis has been done can be summarized as follows: 1. Learning of the discovery method of learning methods had a positive impact in improving student achievement marked by increased mastery learning students in each cycle, i.e the first cycle (48.72%), the second cycle (91.89%), while for the affective domain is the first cycle (69.23%), the second cycle (91.89%), 2. to increase students' motivation as indicated by the average response of students stating that the student interested in and interested in learning methods discovery method so that they become motivated to learn.